The Illusion of trust : toward a medical theological ethics in the postmodern age - DuBose, Edwin R (Kluwer Academic Press, 1995)
The vulnerability of the ill highlights the importance of trust in physician--patient relationships. Previous work in theological ethics on the fiduciary principle or the virtue of trust has not fully appreciated the effect on relations between physicians and patients of a professional and organizational frame of reference grounded in the image of the physician as keeper of knowledge and expertise. In recent years, these relationships have been characterized by an economy of domination in which the physician or patient secures his or her autonomy at the expense of the other; trust becomes a commodity bartered between self-interested parties. As a result, the profession\'s traditional declaration of a commitment to the patient\'s interests is becoming illusory. If God is envisioned as a presence enriched by relationship with humans, trust-as-faith or a commitment to trust in spite of our vulnerability becomes the basis for social relationships of mutual dependency and a model for the physician--patient relationship. The book will be of interest to moral philosophers, physicians, religious ethicists, and theologians. It is suitable for use as a textbook and as supplementary reading in graduate courses in philosophy of medicine, theological ethics, and medical ethics.
Theology and medicine ; Vol. 5
Keywords: etika, bioetika, lékařská etika